The level of awareness of people on grey water harvesting and rainwater harvesting to solve water issues in Kelantan during floods / Nur Hamizah binti Suhaimi and Nur Azfahani binti Ahmad - Suhaimi, Nur Hamizah; Ahmad, Nur Azfahani (2019)
In 2014, major floods have occurred in the east coast states especially in Kelantan. The floods have crippled nearly 80% of the districts in Kelantan. This natural disaster has caused water supply to be cut off throughout the affected areas. Therefore, flood victims had to wait for clean water supply to be distributed during large floods from the government and the private sector. The purpose of this study was to measure the level of flood victims' awareness of Gray Water and Rain Water Harvesting Technology which gave alternative to flood victims to get clean water supply and introduced Grey Water and Rain Water Harvesting Technology that could be used during the large flood supply clean water through stored waste water and filtered rain water. This study was conducted in areas affected by floods such as Kuala Krai, Machang and Tanah Merah using qualtative and quantitative method. Through this research method, 89% of flood victims unaware about Rain Water and Grey Water Harvesting technology. Therefore, the government or the private sector should take the initiative to introduce this technology to be provided at flood evacuation centers and at flood victims' homes.